UiTM sealed MoUs and MoAs with Skyline University, EUMMAS, and City University Ajman in Dubai - Bahrudin, Nur Zahidah (UiTM, 2023)
UiTM formalized collaborations through MoUs and MoAs with Skyline University, EUMMAS, and City University Ajman in Dubai, aiming to strengthen academic partnerships, research collaboration, and student exchange opportunities.